An Interdisciplinary Scoping Review of Sustainable E-Learning within Human Resources Higher Education Provision - McCotter, Sinéad (Sustainability, 2023)
Background: This paper has identified a gap in the extant Human Resource higher education literature in relation to the use of sustainable e-learning pedagogy. As such, a scoping review has been undertaken to draw conclusions to help narrow this gap. This review is timely, given the rise in e-Human Resource practices in organisations. Introduction: For Human Resource e-learning to be truly sustainable, consideration also needs to be given to the broader driving forces impacting its long-term viability in university provision. The objectives of this paper are focused on exploring the interdisciplinary nature of the context, challenges, benefits, and future directions of sustainable e-learning in tertiary education. Design: the methodological design is based upon the PRISMA extension for scoping reviews. Discussion: this scoping review also considers the emerging e-learning sustainability issues at the university level to determine if a full systematic literature review would be beneficial in the long term. Conclusions: this paper offers conclusions to support Human Resource researchers and educators who wish to push the boundaries of sustainable e-learning research. Future Direction: this paper also points to the speed of advances in AI and the need to move from a uni-generational to a multi-generational sustainable e-learning focus.